Pembangunan Sistem Informasi Manajemen dan Pelayanan Konsumen PT. Air Minum Giri Menang (PERSERODA) - Rifqi Hammad; Habib Ratu Perwira Negara; Ahmad Ahmad; Muhammad Arfa; Lalu Erwin Jannata Arhaditya (LPPM Universitas Bumigora, 2022)
PT. Air Minum Giri Menang is a drinking water service provider company located in the city of Mataram. The existence of news media and information on consumer complaints is also one of the services provided by this company, where consumers can easily get updates from the latest news about drinking water services, but the management of this information is still somewhat inefficient because the categories of Latest News and Disturbance Information are still managed by a different admin. This activity is carried out by the service team as a form of applying knowledge to help the community. The method used is the Waterfall method which makes it easier to build the system to be achieved. The purpose of this activity is to build an information portal and complaint service, as well as build a system that can help admins from PT. Air Minum Giri Menang manages news information and consumer complaints in one place. Based on the results of the test cases, it can be concluded that the application can run well and in accordance with the desired results regardless of the type of device the application is accessed from.